Design and Development of a Mobile-Based “Sembako” Application Using Flutter - Nadia Nadia; Yulhendri Yulhendri (Yayasan Literasi Sains Indonesia, 2025)
The rapid development of information technology has transformed the way people conduct business transactions, shifting from traditional face-to-face methods to online systems through e-commerce platforms. However, challenges remain in ensuring equitable access to essential goods, particularly for communities with limited distribution networks. This study aims to design and develop a mobile-based Sembako (basic commodities) application using the Flutter framework to improve efficiency, accessibility, and user experience in purchasing daily necessities. The research employed the Waterfall method within the System Development Life Cycle (SDLC), involving stages of planning, analysis, design, implementation, and testing. Data were collected through observation, interviews, and literature studies conducted at an MSME store in Central Jakarta. The system was developed using Dart for programming and Firebase as the database for real-time data management. Results showed that the Sembako application successfully met functional requirements, enabling efficient management of stock, transactions, and digital payments while achieving a high user satisfaction score of 4.82 out of 5 in User Acceptance Testing. The study contributes to the advancement of mobile commerce by offering a practical and scalable solution for digital transformation in MSMEs, although future improvements should integrate loyalty systems and automated customer services.